2006
DOI: 10.1590/s0037-86822006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy, immunochemotherapy and chemotherapy for American cutaneous leishmaniasis treatment

Abstract: The first choice of treatment for American cutaneous leishmaniasis is the pentavalent antimonial drug. Although it has been shown that this treatment is mostly effective and indicated, some disadvantages should be taken into account such as side effects, long term treatment inconveniences and counter-indication for patients suffering from cardiopathy, nephropathy; yet, aging, pregnancy and other conditions. With the advent of the vaccine anti-American cutaneous leishmaniasis as a prophylactic measure, studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 54 publications
0
31
0
6
Order By: Relevance
“…Indeed, when compared with conventional therapy, L. amazonensis vaccine treatment reduced the time necessary for lesions in patients with cutaneous leishmaniasis to completely heal (Toledo et al 2001). Furthermore, Mayrink et al (2006) have shown that the association of a vaccine antigen with antimonium salts reduces both the total salt volume and the treatment length, thereby reducing the side effects otherwise associated with the use of antimonium salts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when compared with conventional therapy, L. amazonensis vaccine treatment reduced the time necessary for lesions in patients with cutaneous leishmaniasis to completely heal (Toledo et al 2001). Furthermore, Mayrink et al (2006) have shown that the association of a vaccine antigen with antimonium salts reduces both the total salt volume and the treatment length, thereby reducing the side effects otherwise associated with the use of antimonium salts.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, dead promastigotes were used for the development of prophylactic vaccines in Brazilian patients. 10 The work by Pereira and others 11 reported the use of a vaccine containing killed promastigotes of Leishmania associated with the Bacillus Calmette-Guerin (BCG) alone or combined with chemotherapy. This vaccine may an alternative for patients who are intolerant or resistant to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Immunochemotherapy (vaccine with antileishmanial drugs) is maybe an alternative treatment for those patients for whom SbV compounds are not indicated, clinical trial guidelines are being generate 7,11,16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias and sudden death have been reported with doses greater than 20 mg of SbV/kg body weight/day. Pentavalent antimonials should be used with caution in elderly patients and those with heart disease, nephropathy and in pregnancy 5,11,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation